Interactive Intelligent Software System and NLP Techniques for Document Processing - G Desai, Prashant; H, Sarojadevi; N Chiplunkar, Niranjan (International Journal of Engineering and Technology, 2018)
The text written within the documents in different formats contains valuable information. Since the quantum of this kind of unstructured text to be processed is very large, a lot of research has taken place towards finding an intelligent system which helps in discovering the valuable information. The proposed research has developed a software system with the objective of processing natural language text and producing results of importance. This paper presents two new algorithms for document processing. The first algorithm interacts with users to find shorter answers using the query submitted by the user. The results show a precision of 80%. The second algorithm is based on the concept of a template prepared and input by the human. It is employed for representing the original document in a concise format.Â The experimental results obtained and evaluated with the help of metrics from within the domain demonstrate that an accuracy of 73% can be achieved.Â Â